Slamet Diharjo Dalam Pelestarian Tari Lundoyo di Desa Kemiren - Muhammad Gilang Ilham Wahyuda; Dhimas Arif Affandhy (Jurnal Sitakara, 2023)
In the current period, Banyuwangi arts have experienced a decline in interest due to the times, but traditional communities still maintain existing arts as a forum for cultural preservation, one type of art is Barong Lundoyo which can be interpreted as one of the most valuable barongs inherited by Wong Osing ancestors. With this art's presence, one artist made a dance work, namely the Lundoyo Dance. Slamet Diharjo is an art activist who created Lundoyo Dance in 2013. Rituals held in Banyuwangi always involve performing arts. In preparing this Lundoyo Dance, Slamet Diharjo poured elements ranging from movement, music, makeup, and property. As the inheritor of cultural preservation, Slamet Diharjp hopes that young people today will remember their culture. This dance contains a message that if we do wrong, it will disappear with goodness in life. Keywords: Tradition Preservation; Barong Lundoyo; Dance Meaning